PENERAPAN MODEL CONTEXTUAL TEACHING AND LEARNING (CTL) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SD NEGERI 8 PEKANBARU - Juliana Juliana; Jesi Alexander Alim; Syahrilfuddin Syahrilfuddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstarck : This was a classroom research (PTK) which has two cycles which was conducted on March – April 2015. The data shown the either learning process increased. The basic score of daily examination as 11,92% which 20 students passed and 10 students failed. The ending of daily examination was 75% and the average was 76,8% on the passing grade. The second daily examination also increased from basic score as 17,12% which 30 students passed and nothing students failed. The ending of second daily examination was 87,5% and the average was 100. Based on the explanation above it can be concluded that the implementation of contextual teaching and learning (CTL) increased students’ achievement the result of science studies of students IV grade of State Elementary School 8 Pekanbaru.Keywords : Contextual Teaching and Learrning(CTL), Students Achievement The Result Of Science Studies